A Comparison of Surface Passivation Techniques for Measurement of Minority Carrier Lifetime in Thin Si Wafers: Toward a Stable and Uniform Passivation. Issue 1670 (17th June 2014) - Sopori, Bhushan; Devayajanam, Srinivas; Basnyat, Prakash; Mehta, Vishal; Moutinho, Helio; Nemeth, Bill; LaSalvia, Vincenzo; Johnston, Steve; Ravindra, N.M.; Binns, Jeff; Appel, Jesse
ABSTRACT: We describe appropriate wafer cleaning procedure and surface passivation characteristics of various passivants used for making measurement of minority carrier lifetime (τB ) of very high quality Si wafers. These passivants include: iodine ethanol (I-E), quinhydrone methanol (QH-M), SiO2, and Al2 O3 . The issues related to the passivation stability and the spatial uniformity for mapping τB are also discussed.